Association of selenium intake with bone mineral density and osteoporosis: the national health and nutrition examination survey - Peng, Shiyu; Zhang, Gaoxiang; Wang, Decheng (Frontiers in Endocrinology, 2023)
Background Osteoporosis (OP) is a systemic metabolic skeletal disorder characterized by a decrease in bone mineral density (BMD) and an increase in the risk of fracture. The level of selenium (Se) in serum is associated with BMD. However, the relationship between dietary and total selenium intake and parameters such as osteoporosis and BMD is unclear. By conducting National Health and Nutritional Examination Surveys (NHANES), in this study, we assessed the association of Se intake with BMD and the risk of OP among general middle-aged and elderly people. Methods The data were collected from three cycles of NHANES [2009–2010, 2013–2014, and 2017–2020]. Information on the dietary and supplementary Se intake was obtained from 24-h dietary recall interviews. Additionally, dual-energy X-ray absorptiometry (DXA) was performed to measure BMD, which was later transformed into T-scores; OP was diagnosed when the T-score was ≤ -2.5. We constructed a logistic regression model for the association between selenium intake and the risk of OP based on the estimated odds ratios (ORs) and the 95% confidence intervals (CIs). We also constructed a multivariable linear regression model to analyze the relationship between selenium intake and BMD. Results In this study, 3,250 individuals (average age: 60.01 ± 10.09 years; 51.88% females) participated. The incidence of OP was 9.35% (3.30% for males and 17.75% for females). In the logistic regression model adjusted for every interested covariate, a higher quartile of dietary Se intake (OR for quartile 4 vs. quartile 1: 0.63; 95% CI: 0.41–0.96; P for trend = 0.027) was related to a lower risk of OP relative to the lowest quartile. The total selenium intake also exhibited a consistent trend (OR for quartile 4 vs. quartile 1: 0.67; 95% CI: 0.44–1.01; P for trend = 0.049). The results of the adjusted multivariate linear regression model showed that the participants with the highest quartile of dietary Se intake (Q4) had higher BMD in the total femur (β = 0.069, P = 0.001; P for trend = 0.001), femoral neck (β = 0.064, P = 0.001; P for trend = 0.001), and total spine (β = 0.030, P = 0.136; P for trend = 0.064) compared to those in quintile 1 (Q1). A similar trend of associations was observed for the total selenium intake with BMD, which was more prominent among females, as determined by the subgroup analysis. Conclusion In this study, the dietary intake and total intake of selenium were positively associated with BMD, whereas they were negatively associated with the risk of OP among adults in the US. Further studies are required to verify our results and elucidate the associated biological mechanism.